2021
DOI: 10.1155/2021/8883040
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hepatoprotective Activity of Caralluma europaea Stem Extract against CCl4-Induced Hepatic Damage in Wistar Rats

Abstract: The present study aims to evaluate the hepatoprotective activity of stem aqueous extract of Caralluma europaea (AECe) on carbon tetrachloride- (CCl4-) induced hepatic damage in Wistar rats. The animals were daily treated with the aqueous extract of C. europaea at a dose of 250 mg/kg body weight for 14 days. CCl4 was injected (1 ml/kg, i.p.) two times, on the 7th and 14th days. At the end of the experimental period, all rats were anesthetized to collect blood for the assessment of biochemical parameters and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
3
8
0
2
Order By: Relevance
“…In the current work and in line with Ouassou et al [32] and Sharma and Shukla [33], the more time of rats exposure to CCl4 exerted the more AST, ALT, and ALP rise in sera definitely at the expense of their presence within hepatic tissue signifying their infiltration through hepatic cell membranes or even their release into the bloodstream following cell death. Interestingly, the increase in the complex dose coadministered with CCl4 to 2.4 mg/kg produces a pronounced significant decrease in these activities.…”
Section: Discussionsupporting
confidence: 87%
“…In the current work and in line with Ouassou et al [32] and Sharma and Shukla [33], the more time of rats exposure to CCl4 exerted the more AST, ALT, and ALP rise in sera definitely at the expense of their presence within hepatic tissue signifying their infiltration through hepatic cell membranes or even their release into the bloodstream following cell death. Interestingly, the increase in the complex dose coadministered with CCl4 to 2.4 mg/kg produces a pronounced significant decrease in these activities.…”
Section: Discussionsupporting
confidence: 87%
“…The results of current study demonstrated that AgNPs and chicory formulation extract possessed remarkable hepato-protective potential ( Table 3 ). The hepato-protective activity of a plant depends upon the ability to ameliorate the toxic effect or maintain normal physiological functions ( Ouassou et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The liver is the prime organ in the human body that helps in maintaining metabolic and physiologic homeostasis. It plays a central and important role in many metabolic pathways especially those related to growth and development, fighting off diseases, production and supply of nutrients and energy, metabolism of proteins, carbohydrates and fats, bile secretion and storage of vitamins (Ouassou et al, 2021;Sami et al, 2019, Tafere et al, 2019Ugwu & Suru 2021;Wahid et al, 2016). Furthermore, the liver is also a crucially important organ in drug metabolism and protecting humans against the harmful impact of many toxic agents.…”
Section: Introductionmentioning
confidence: 99%